Activated History - The Case of the Turkish Sieges of Vienna - Christian Ochsner; Felix Rösel (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study whether long-gone but activated history can shape social attitudes and behavior even after centuries. We exploit the case of the sieges of Vienna in 1529 and 1683, when Turkish troops pillaged individual municipalities across East Austria. In 2005, Austrian right-wing populists started to campaign against Turks and Muslims and explicitly referred to the Turkish sieges. We show that right-wing voting increased in once pillaged municipalities compared to non-pillaged municipalities after the campaigns were launched, but not before. The effects are substantial: Around one out of ten votes for the far-right in a once pillaged municipality is caused by salient history. We conclude that campaigns can act as tipping points and catalyze history in a nonlinear fashion.
Keywords: D72; N43; N44; Z13; 330; salience; persistence; right-wing populism; political campaigns; collective memory; Turkish sieges; Austria